The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Academic achievements after childhood meningitis: a nationwide, population-based cohort study - Emma E. Graham; Malte M. Tetens; Jacob Bodilsen; Nanna S. Andersen; Ram Dessau; Svend Ellermann-Eriksen; Kristina Franck; Sofie Midgley; Jens Kjølseth Møller; Alex Christian Nielsen; Lene Nielsen; Kirstine K. Søgaard; et al. (Infectious Diseases, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Geochronology, mineral chemistry, and geochemistry of kimberlites from Victoria Island, Arctic Canada - Alex A. Müller; Chiranjeeb Sarkar; Bruce A. Kjarsgaard; James LeBlanc; Soumendu Sarkar; Sarah J. Woodland; D. Graham Pearson (Mineralogy and Petrology, 2025)

Decision-making and ecosystem service dimensions of managed dyke realignment in the complex coastal landscapes of the Bay of Fundy - Lara Cornejo; Elson Ian Nyl Ebreo Galang; Kate Sherren; Jeremy Lundholm; Danika van Proosdij; Will Balser; Elena Bennett; Tony M. Bowron; Kirsten Ellis; Jonathan Fowler; Jennifer Graham; Patrick James; et al. (Ocean & Coastal Management, 2025)

Future climate projections in the global coastal ocean - Jason Holt; Anna Katavouta; Joanne Hopkins; Laurent O. Amoudry; Christian M. Appendini; Lars Arneborg; Alex Arnold; Yuri Artioli; Jerome Aucan; Barbara Berx; Laura Cagigal; Michela De Dominicis; et al. (Progress in Oceanography, 2025)

Remote sensing of electron precipitation mechanisms enabled by ELFIN mission operations and ADCS - Ethan Tsai; Akhil Palla; Austin Norris; James King; Cindy Russell; Sophie Ye; Jiashu Wu; Jason Mao; Sharvani Jha; Chanel Young; Graham Wing; Kevin Lian; et al. (Advances in Space Research, 2025)

Trees, terraces and llamas: Resilient watershed management and sustainable agriculture the Inca way - Michael R. Frogley; Alex Chepstow-Lusty; Graham Thiele; Constantino Aucca Chutas (Ambio, 2025)
The Inca and their immediate predecessors provide an exceptional model of how to create high-altitude functional environments that sustainably feed people with a diversity of crops, whilst mitigating erosion, protecting forestry and maintaining soil fertility without the need for large-scale burning. A comparison is provided here of landscape practices and impacts prior to and after the Inca, derived from a unique 4200-year sedimentary record recovered from Laguna Marcacocha, a small, environmentally sensitive lake located at the heart of the Inca Empire. By examining ten selected proxies of environmental change, a rare window is opened on the past, helping to reveal how resilient watershed management and sustainable, climate-smart agriculture were achieved. We contend that, in the face of modern environmental uncertainty, a second climate-smart agricultural revolution is necessary, but one that accounts for the significant social capital of highland communities whilst still leaning heavily on native crops, trees and livestock.

Hemisphere- and condition-specific alpha oscillations support semantic and spatial cognition in aging - Maggie P. Rempe; Danae S. Manta; Kayle Cohen; Ryan J. Glesinger; Hannah J. Okelberry; Jason A. John; Anna T. Coutant; Lucy K. Horne; Grant M. Garrison; Kennedy A. Kress; Lucas Weyrich; Chloe C. Casagrande; et al. (GeroScience, 2025)

Risk of psychiatric neurodevelopmental disorders after meningitis in childhood: a nationwide, population-based cohort study - Emma E. Graham; Malte M. Tetens; Jacob Bodilsen; Ram Dessau; Svend Ellermann-Eriksen; Nanna S. Andersen; Charlotte Sværke Jørgensen; Michael Pedersen; Kirstine K. Søgaard; Jette Bangsborg; Alex Christian Nielsen; Jens Kjølseth Møller; et al. (Infectious Diseases, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Interplay of egg white gel pH and intragastric pH: Impact on breakdown kinetics and mass transport processes - Alisha Kar; Alex G. Olenskyj; Maria Garcia Guerrero; Riley Graham; Gail M. Bornhorst (Food Research International, 2023)

Challenges in cybersecurity: Lessons from biological defense systems - Edward Schrom; Ann Kinzig; Stephanie Forrest; Andrea L. Graham; Simon A. Levin; Carl T. Bergstrom; Carlos Castillo-Chavez; James P. Collins; Rob J. de Boer; Adam Doupé; Roya Ensafi; Stuart Feldman; et al. (Mathematical Biosciences, 2023)

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Environmental DNA Based Surveillance for the Highly Invasive Carpet Sea Squirt Didemnum vexillum: A Targeted Single-Species Approach - Iveta Matejusova; Jennifer Graham; Fiona Bland; Jean-Pierre Lacaze; Guillaume Herman; Lyndsay Brown; Eric Dalgarno; John D. Bishop; Jenni E. Kakkonen; Kirsty F. Smith; Alex Douglas (Frontiers in Marine Science, 2021)
The presence and diversity of marine non-native species, the number of new invasions, and the impact on native communities and habitats are important metrics used to assess the health of marine ecosystems. Monitoring for marine non-native species, using traditional approaches such as rapid assessment surveys (RASs), requires taxonomic expertise and may still fail to detect rare or inconspicuous species. This study reports a validation process for a quantitative PCR (qPCR) assay based on the cytochrome oxidase 1 gene, designed to detect highly invasive tunicate Didemnum vexillum by targeting environmental DNA (eDNA) present in water samples. The D. vexillum qPCR assay showed high sensitivity, with the threshold limit of detection (LOD) and modeled LOD3 (based on triplicate qPCR reactions) estimated as 9.187 and 1.117 copies reaction –1 , respectively and the limit of quantification (LOQ) was calculated as 18 copies reaction –1 . Analyses of water samples collected from selected Pacific oyster farms and recreational marinas in Scotland showed 100% concordance between the historical data on presence of D. vexillum from RASs and detection of D. vexillum eDNA. Consistency of detection of D. vexillum eDNA among different sampling points within each infected sampling site varied, ranging between 100% positive throughout the site to some sampling points testing “negative” or only as “suspected” for D. vexillum . Sites with lower within-site detection consistency included sites with a low density of D. vexillum as reported by RASs or were sites undergoing D. vexillum management. The present pilot monitoring program demonstrates the potential to generate important data on presence of D. vexillum . This program will be scaled up across large geographic regions and used in the first instance to focus and target the traditional RASs to D. vexillum eDNA-positive sites in a cost-effective way, with an aim to verify the species presence by visual observation and direct Sanger sequencing of positive qPCR products.

What drives study‐dependent differences in distance–decay relationships of microbial communities? - Dave R. Clark; Graham J.C. Underwood; Terry J. McGenity; Alex J. Dumbrell (Global Ecology and Biogeography, 2021)
Aim Ecological communities that exist closer together in space are generally more compositionally similar than those far apart, as defined by the distance–decay of similarity relationship. However, recent research has revealed substantial variability in the distance–decay relationships of microbial communities between studies of different taxonomic groups, ecosystems and spatial scales and between those using different molecular methodologies (e.g., high‐throughput sequencing versus molecular fingerprinting). Here, we test how these factors influence the strength of microbial distance–decay relationships, in order to draw generalizations about how microbial β‐diversity scales with space. Location Global. Time period Studies published between 2005 and 2019 (inclusive). Major taxa studied Bacteria, Archaea and microbial Eukarya. Methods We conducted a meta‐analysis of microbial distance–decay relationships, using the Mantel correlation coefficient as a measure of the strength of distance–decay relationships. Our final dataset consisted of 452 data points, varying in environmental/ecological context or methodological approaches, and we used linear models to test the effects of each variable. Results Both ecological and methodological factors had significant impacts on the strength of microbial distance–decay relationships. Specifically, the strength of these relationships varied between environments and habitats, with soils showing significantly weaker distance–decay relationships than other habitats, whereas increasing spatial extents had no effect. Methodological factors, such as sequencing depth, were positively related to the strength of distance–decay relationships, and choice of dissimilarity metric was also important, with phylogenetic metrics generally giving weaker distance–decay relationships than binary or abundance‐based indices. Main conclusions We conclude that widely studied microbial biogeographical patterns, such as the distance–decay relationship, vary by ecological context but are primarily distorted by methodological choices. Consequently, we suggest that by linking methodological approaches appropriately to the ecological context of a study, we can progress towards generalizable biogeographical relationships in microbial ecology.

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

The North American Forest Database: going beyond national-level forest resource assessment statistics - W. Brad Smith; Rubí Angélica Cuenca Lara; Carina Edith Delgado Caballero; Carlos Isaías Godínez Valdivia; Joseph S. Kapron; Juan Carlos Leyva Reyes; Carmen Lourdes Meneses Tovar; Patrick D. Miles; Sonja N. Oswalt; Mayra Ramírez Salgado; Xilong Alex Song; Graham Stinson; et al. (Environmental Monitoring and Assessment, 2018)

The effects of fluoxetine on attachment and righting behaviours in marine (Gibbula unbilicalis) and freshwater (Lymnea stagnalis) gastropods - Alex T. Ford; Bernice Hyett; Daniel Cassidy; Graham Malyon (Ecotoxicology, 2018)

Biogeography at the limits of life: Do extremophilic microbial communities show biogeographical regionalization? - Dave R. Clark; Mégane Mathieu; Léonie Mourot; Laurent Dufossé; Graham J. C. Underwood; Alex J. Dumbrell; Terry J. McGenity (Global Ecology and Biogeography, 2017)
Aim Biogeographical regions are the fundamental geographical units for grouping Earth's biodiversity. Biogeographical regionalization has been demonstrated for many higher taxa, such as terrestrial plants and vertebrates, but not in microbial communities. Therefore, we sought to test empirically whether microbial communities, or taxa, show patterns consistent with biogeographical regionalization. Location Within halite (NaCl) crystals from coastal solar salterns of western Europe, the Mediterranean and east Africa. Time period Modern (2006–2013). Major taxa studied Archaea. Methods Using high‐throughput Illumina amplicon sequencing, we generated the most high‐resolution characterization of halite‐associated archaeal communities to date, using samples from 17 locations. We grouped communities into biogeographical clusters based on community turnover to test whether these communities show biogeographical regionalization. To examine whether individual taxa, rather than communities, show biogeographical patterns, we also tested whether the relative abundance of individual genera may be indicative of a community's biogeographical origins using machine learning methods, specifically random forest classification. Results We found that the rate of community turnover was greatest over subregional spatial scales ( Main conclusions Overall, our results provide little support for the concept of biogeographical regions in these extremophilic microbial communities, despite the fact that some taxa do show biogeographical patterns. We suggest that variable dispersal ability among the halite‐associated Archaea may disrupt biogeographical patterns at the community level, preventing the formation of biogeographical regions. This means that the processes that lead to the formation of biogeographical regions operate differentially on individual microbial taxa rather than on entire communities.

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Shooting fish in a barrel? Assessing fisher‐driven changes in catchability within tropical tuna purse seine fleets - Alex Tidd; Stephen Brouwer; Graham Pilling (Fish and Fisheries, 2017)
With constant innovation to find more efficient ways to find, catch and process fish, catchability in wild fisheries can increase. Catchability is a combination of resource abundance, fishing effort and fishing efficiency: any increase in fleet efficiency can lead to undesirable effects not only on stocks, but also on the ability to assess them. When using effort controls as part of management, it is necessary to adjust for the increase in catchability due to the increases in efficiency over time to avoid stock depletion. Accounting for changes in catchability can be problematic for pelagic stocks, due to the changes in fishing behaviour and the continual change in fishing efficiency. This study investigates the success in finding patches of fish for fleets operating within the western and central Pacific purse seine fishery between 1993 and 2012. Three indices, widely used in ecological research, were used to study how spatial variation in fisher behaviour for sets on fish aggregating devices ( FAD s) and free‐school sets was related to catchability. For free‐school set types, the diversity index was negatively correlated with Katsuwonus pelamis catchability. When this index was low, catch rates were at their highest and there was a reduction in the area fished. In contrast, for FAD sets, catches increase when the patchiness index was low, implying a degree of random behaviour, potentially due to advances in FAD technology. An improved understanding of the spatial allocation of effort can improve catchability estimates widely used for fisheries stock assessments and in indices of global biodiversity.

Deterministic influences exceed dispersal effects on hydrologically‐connected microbiomes - Emily B. Graham; Alex R. Crump; Charles T. Resch; Sarah Fansler; Evan Arntzen; David W. Kennedy; Jim K. Fredrickson; James C. Stegen (Environmental Microbiology, 2017)
Summary Subsurface groundwater‐surface water mixing zones (hyporheic zones) have enhanced biogeochemical activity, but assembly processes governing subsurface microbiomes remain a critical uncertainty in understanding hyporheic biogeochemistry. To address this obstacle, we investigated (a) biogeographical patterns in attached and waterborne microbiomes across three hydrologically‐connected, physicochemically‐distinct zones (inland hyporheic, nearshore hyporheic and river); (b) assembly processes that generated these patterns; (c) groups of organisms that corresponded to deterministic changes in the environment; and (d) correlations between these groups and hyporheic metabolism. All microbiomes remained dissimilar through time, but consistent presence of similar taxa suggested dispersal and/or common selective pressures among zones. Further, we demonstrated a pronounced impact of deterministic assembly in all microbiomes as well as seasonal shifts from heterotrophic to autotrophic microorganisms associated with increases in groundwater discharge. The abundance of one statistical cluster of organisms increased with active biomass and respiration, revealing organisms that may strongly influence hyporheic biogeochemistry. Based on our results, we propose a conceptualization of hyporheic zone metabolism in which increased organic carbon concentrations during surface water intrusion support heterotrophy, which succumbs to autotrophy under groundwater discharge. These results provide new opportunities to enhance microbially‐explicit ecosystem models describing hyporheic zone biogeochemistry and its influence over riverine ecosystem function.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Soil compartment is a major determinant of the impact of simulated rainfall on desert microbiota - Shazia N. Aslam; Alex J. Dumbrell; Jamal S. Sabir; Mohammed H. Z. Mutwakil; Mohammed M. N. Baeshen; Salah E. M. Abo‐Aba; Dave R. Clark; Steven A. Yates; Nabih A. Baeshen; Graham J. C. Underwood; Terry J. McGenity (Environmental Microbiology, 2016)
Summary Although desert soils support functionally important microbial communities that affect plant growth and influence many biogeochemical processes, the impact of future changes in precipitation patterns on the microbiota and their activities is largely unknown. We performed in‐situ experiments to investigate the effect of simulated rainfall on bacterial communities associated with the widespread perennial shrub, Rhazya stricta in Arabian desert soils. The bacterial community composition was distinct between three different soil compartments: surface biological crust, root‐attached, and the broader rhizosphere. Simulated rainfall had no significant effect on the overall bacterial community composition, but some population‐level responses were observed, especially in soil crusts where Betaproteobacteria, Sphingobacteria, and Bacilli became more abundant. Bacterial biomass in the nutrient‐rich crust increased three‐fold one week after watering, whereas it did not change in the rhizosphere, despite its much higher water retention. These findings indicate that between rainfall events, desert‐soil microbial communities enter into stasis, with limited species turnover, and reactivate rapidly and relatively uniformly when water becomes available. However, microbiota in the crust, which was relatively enriched in nutrients and organic matter, were primarily water‐limited, compared with the rhizosphere microbiota that were co‐limited by nutrients and water.

How do field of view and resolution affect the information content of panoramic scenes for visual navigation? A computational investigation - Antoine Wystrach; Alex Dewar; Andrew Philippides; Paul Graham (Journal of Comparative Physiology A, 2016)

A road map for molecular ecology - Rose L. Andrew; Louis Bernatchez; Aurélie Bonin; C. Alex. Buerkle; Bryan C. Carstens; Brent C. Emerson; Dany Garant; Tatiana Giraud; Nolan C. Kane; Sean M. Rogers; Jon Slate; Harry Smith; et al. (Molecular Ecology, 2013)
The discipline of molecular ecology has undergone enormous changes since the journal bearing its name was launched approximately two decades ago. The field has seen great strides in analytical methods development, made groundbreaking discoveries and experienced a revolution in genotyping technology. Here, we provide brief perspectives on the main subdisciplines of molecular ecology, describe key questions and goals, discuss common challenges, predict future research directions and suggest research priorities for the next 20 years.

Expression of stromal genes associated with the angiogenic response are not differentiated between human tumour xenografts with divergent vascular morphologies - Matthew Farren; Susie Weston; Helen Brown; Nicola Broadbent; Steve Powell; Robert Shaw; Neil R. Smith; Rachael Inglis; Alex Graham; Sue Ashton; Stephen R. Wedge; Simon T. Barry (Angiogenesis, 2012)

Screening practices of Australian men and women categorized as “at or slightly above average risk” of colorectal cancer - Driss Ait Ouakrim; Trevor Lockett; Alex Boussioutas; Louise Keogh; Louisa B. Flander; Ingrid Winship; Graham G. Giles; John L. Hopper; Mark A. Jenkins (Cancer Causes & Control, 2012)

Silviculture and Forest Ecology - David Mercker; Ryan Blair; Don Tyler; Theresa Jain; Russell Graham; Donald Rockwood; Nicholas Koch; Jeremy Brawner; Omar Carrero; Kristofer Covey; Alex Barrett; Mark Ashton; et al. (Journal of Forestry, 2011)
2Over the past several decades, federal incentive programs have encouraged the restoration of bottomland forests throughout the West Gulf Coastal Plain (WGCP) and the Lower Mississippi Alluvial Valley (LMAV). Programs such as the Conservation Reserve (CRP) and Wetlands Reserve (WRP) Programs have been marginally successful (Stanturf et al. 2001). Foresters and contractors often follow conventional tree planting procedures that are well established for upland sites, but prove problematic in bottomlands. High water tables, soil drainage and compaction, overland flooding and diverse soil properties make species selection difficult. Slight changes in topography and soil structure often have a dramatic effect on survival and growth of planted oak seedlings (Hodges and Schweitzer 1979). This project documented the survival and growth of six-year old seedlings that were established on a bottomland site in 2004, located at the West Tennessee Research and Education Center, Jackson, Tennessee. The purpose was to determine how soil drainage as indicated by mottling (specifically, the point of 50 percent gray color throughout the soil profile) affects the survival and growth of bottomland oak species. The findings suggest that practitioners plant Nuttall, pin and overcup oaks in poorly drained soils. As the drainage improves, begin mixing in willow oak. In the best drained soils (if they exist), finish by including water, swamp chestnut, swamp white, Shumard, cherrybark and bur oaks. Potential species diversity should expand as the soil drainage improves.

Coccolithophore dynamics in non‐bloom conditions during late summer in the central Iceland Basin (July‐August 2007) - Alex J. Poulton; Anastasia Charalampopoulou; Jeremy R. Young; Glen A. Tarran; Mike I. Lucas; Graham D. Quartlya (Limnology and Oceanography, 2010)
Measurements of primary production (PP), calcification (CF), and coccolithophore abundance were made during late summer (July‐August 2007) in the Iceland Basin. Low numbers of coccolithophore cells and detached coccoliths ( 3 cells mL −1 and 1‐15 × 10 3 coccoliths mL −1 , respectively) indicated a non‐bloom community, with Emiliania huxleyi as the dominant coccolithophore in terms of abundance, coccolithophore organic biomass, and cell calcite. PP ranged from 0.1 to 2 [mol C m −3 d −1 , while CF ranged from 10 to 250 [mol C m −3 d −1 , with both typically decreasing with depth. Coccolithophores were estimated to contribute 10‐20% toward total chlorophyll a , phytoplankton carbon, and PP within the euphotic zone. In these non‐bloom conditions, ~ 30‐60% of the total calcite in the water column was present as detached coccoliths rather than whole cells. Both cell numbers and variability in cell‐normalized CF controlled the magnitude of total CF, and hence both physiological limits to cell CF and growth, as well as mortality factors, need to be taken into account when examining oceanic coccolithophore communities. Combining cell‐normalized CF with an estimate of coccolith calcite gave coccolith production rates (0.4‐1.8 h −1 ) similar to those reported in the literature for laboratory cultures of E. huxleyi . None of the factors currently associated with coccolithophore blooms (irradiance, mixed‐layer depth, nitrate, phosphate, or calcite saturation) showed a clear correlation with community or cellular CF. Hence, although mortality is likely to control cell numbers, other factors such as trace metal (iron) availability may influence coccolithophore physiology in the central Iceland Basin during late summer.

Identifying essential fish habitat for small pelagic species in Spanish Mediterranean waters - Jose M. Bellido; Alex M. Brown; Vasilis D. Valavanis; Ana Giráldez; Graham J. Pierce; Magdalena Iglesias; Andreas Palialexis (Hydrobiologia, 2008)

The phylogeographical clade trade: tracing the impact of human‐mediated dispersal on the colonization of northern Europe by the oak gallwasp Andricus kollari - GRAHAM N. STONE; RICHARD J. CHALLIS; RACHEL J. ATKINSON; GYÖRGY CSÓKA; ALEX HAYWARD; GEORGE MELIKA; SERAP MUTUN; SONJA PREUSS; ANTONIS ROKAS; EBRAHIM SADEGHI; KARSTEN SCHÖNROGGE (Molecular Ecology, 2007)
Human dispersal of organisms is an important process modifying natural patterns of biodiversity. Such dispersal generates new patterns of genetic diversity that overlie natural phylogeographical signatures, allowing discrimination between alternative dispersal mechanisms. Here we use allele frequency and DNA sequence data to distinguish between alternative scenarios (unassisted range expansion and long range introduction) for the colonization of northern Europe by an oak‐feeding gallwasp, Andricus kollari . Native to Mediterranean latitudes from Portugal to Iran, this species became established in northern Europe following human introduction of a host plant, the Turkey oak Quercus cerris . Colonization of northern Europe is possible through three alternative routes: (i) unassisted range expansion from natural populations in the Iberian Peninsula; (ii) unassisted range expansion from natural populations in Italy and Hungary; or (iii) descent from populations imported to the UK as trade goods from the eastern Mediterranean in the 1830s. We show that while populations in France were colonized from sources in Italy and Hungary, populations in the UK and neighbouring parts of coastal northern Europe encompass allozyme and sequence variation absent from the known native range. Further, these populations show demographic signatures expected for large stable populations, rather than signatures of rapid population growth from small numbers of founders. The extent and spatial distribution of genetic diversity in the UK suggests that these A. kollari populations are derived from introductions of large numbers of individuals from each of two genetically divergent centres of diversity in the eastern Mediterranean. The strong spatial patterning in genetic diversity observed between different regions of northern Europe, and between sites in the UK, is compatible with leptokurtic models of population establishment.